The Relationship between Leukocyte Counts and BMI Values in Patients with BTA-Positive Pulmonary Tuberculosis - Sahadewa, Sukma; Durry, Fara Disa (Newinera Publisher, 2024)
Leukocytes are a component of white blood cells which play a role in helping the body fight various infectious diseases. Leukocytes are part of the immune system. While an increased number of leukocytes indicates an inflammatory process, in the case of tuberculosis, the entry of M. Tuberculosis in the body causes the number of leukocytes to increase as a response to the body's immunity. This prompted researchers to be interested in examining the relationship between the number of leukocytes and the BMI value in pulmonary TB sufferers with BTA positive at the Kutorejo Community Health Center, Mojokerto Regency. The population and sample in this study were all patients with pulmonary TB with positive BTA at the Kutorejo Community Health Center, with the number of samples taken from the total population of 25 respondents, this sampling used a total sampling technique. The independent variable used was TB sufferers with positive BTA while the dependent variables were leukocyte count and BMI value. To prove the existence of a relationship between these two variables, a statistical test was carried out using the Spearman correlation test. The results of the research show that there is no relationship between the number of leukocytes and the BMI value in pulmonary TB sufferers with BTA positive at the Kutorejo Community Health Center, Mojok-erto Regency. This is confirmed by the results of the Spearman correlation test analysis which obtained a sig value. = 0.199 (α < 0.05).